From Bildungsroman to Bildungsromance: Physical and Affective War in Chinelo Okparanta’s Under the Udala Trees - Cristina Cruz-Gutiérrez (Revista Alicantina de Estudios Ingleses, 2024)
The bildungsroman has dominated the Nigerian literary landscape since the 1990s with novels such as Chimamanda N. Adichie’s Purple Hibiscus (2004), Unoma Azuah’s Sky-High Flames (2005), Chika Unigwe’s Night Dancer (2012), and Chinelo Okparanta’s Under the Udala Trees (2015). These coming-of-age stories place a special emphasis on the national evolution of Nigeria. Thus, by delving into such interrelation of the national and personal domains, I propose to theorize Under the Udala Trees as a “bildungsromance,” or novel of affective and romantic development. I use the term “bildungsromance” to describe the growth of Okparanta’s protagonist, Ijeoma, as intrinsically associated with the experiences gathered from her affective attachments both in the public and the private spheres. I will analyze Ijeoma’s sentimental relationships as she discovers and naturalizes her queer identity. For this, I will delve into the negative affects − in the form of fear, shame and guilt (Braidotti 2009, 50) − that influence Ijeoma’s experience as a result of her non-conforming to the dictums of Nigerian customary laws. Ironically, such negative affects will be introduced as tightly associated with “the promise of happiness” (Ahmed 2010, 14). In turn, I shall underline the role of Ijeoma’s intimate and romantic relationships in prompting positive forms of affect such as self-love and pride. These affective experiences allow Ijeoma to acquire a critical perspective towards Nigerian customary laws and their impact on identity formation and on what has been referred to as the “democratisation of the private sphere” (Giddens 1992, 184). Ultimately, I will hinge upon Ijeoma’s awareness of her own affective advancements as a key element in her bildungsromance.